The effect of tax avoidance on cost of debt capital: Evidence from Korea1 - H-J. Shin; Y-S. Woo (South African Journal of Business Management, 2017)
This study investigates the relation between tax avoidance and the cost of debt capital and analyzes the effect of the debt ratio and profitability on the relation between tax avoidance and the cost of debt. The results of our empirical analysis are as follows. First, tax avoidance is significantly positively associated with the cost of debt capital. This result shows that tax avoidance is considered as the signal of increasing information risk; thus, investors demand a higher return. Second, the debt ratio decreases the positive relation between tax avoidance and the cost of debt capital. This result indicates that the positive relation between tax avoidance and the cost of debt capital significantly decreases when the debt ratio is high. Finally, we find that the profitability of a company increases the positive relation between tax avoidance and the cost of debt capital. This result means that the cost of debt capital increases as the tax avoidance increase when the profitability of company is favorable. We find that the profitability of a company is one of the critical factors that have an effect on the relation between tax avoidance and the cost of debt capital.
Keywords: 650